Triumph of the city : how our greatest invention makes us richer, smarter, greener, healthier, and happier - Glaeser, Edward L. (Edward Ludwig), 1967- (Penguin Press, 2011)
A pioneering urban economist offers fascinating, even inspiring proof that the city is humanity's greatest invention and our best hope for the future.